RESISTANCE TO STEREOTYPES AND DISCRIMINATION IN ZOOTOPIA (2016) - Yahya, Wirda Humaira; Hikmat, Mahi M (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2024)
Zootopia is an animated film released in 2016 by Walt Disney Animation Studios. This movie not only offers entertainment for various audiences, but also conveys a deep social message about resistance to stereotypes and discrimination. This study uses narrative theory. Todorov (1971) put forward the concept of "equilibrium-disequilibrium-new equilibrium" in narrative structure, which suggests that the story begins in a state of equilibrium, experiences disruption, and finally returns to a new equilibrium. The research method used is a qualitative descriptive approach. The primary data used in this study comes from the film Zootopia (2016). While secondary data comes from articles and film reviews, such as academic articles, film critic reviews, and media analysis regarding Zootopia. This study aims to analyze how Zootopia represents and challenges stereotypes and discrimination through its narrative and characterization. It will explore the strategies and actions used by the characters to defy prejudice and prove their abilities beyond narrow social expectations. Through its complex characters and meaningful plot, the movie invites audiences to reflect on the impact of prejudice and discrimination, and the importance of inclusion and equality.